Comparative efficacy of schroth and core training for early postoperative recovery in adolescent idiopathic scoliosis: A single blind randomized controlled trial - Fanyuan Meng; Kerong Li; Wei Wang; Rui Yang; Cong Wang; Zhi Zhao; Moxian Chen; Lijuan Ao (PLoS ONE, 2026)
Background To evaluate the clinical efficacy of Schroth exercises combined with core training versus core training alone on early trunk balance optimization and functional recovery in adolescent idiopathic scoliosis (AIS) patients following selective thoracic fusion surgery. Methods This single-blinded randomized controlled trial enrolled 46 AIS patients with Lenke1 type configuration who underwent selective thoracic posterior spinal fusion at the Orthopedics Department of the Second Affiliated Hospital of Kunming Medical University. Participants were randomly assigned to either the Schroth exercise combined Core Training (SCT, n = 23) or Core training group (CT, n = 23). The SCT group received Schroth three-dimensional (3D) scoliosis-specific exercises combined with core stabilization training: during the initial 3 postoperative months, they performed core exercises, rotational angular breathing, and daily postural management; during the subsequent 3 months, they engaged in Schroth 3D corrective exercises targeting surgical correction outcomes. The CT group exclusively performed core stabilization training throughout the 6-month postoperative period. Both groups received 40-minute intervention sessions three to four times weekly from discharge to 6 months postoperatively. Assessments were conducted at four time points: preoperatively, at the discharge (postoperative day 7), and at 3 and 6 months postoperatively. Spinal radiographic parameters, paraspinal muscle surface electromyography, core muscle strength and endurance, and SRS-22 questionnaire data were analyzed to evaluate early clinical efficacy across three domains: body structure/function, activities, and participation in surgically treated AIS patients. Results Analysis of the primary radiographic outcomes revealed no significant time-by-group interactions. However, the SCT group demonstrated superior overall improvement in pelvic balance compared to the CT group (Group main effect: p = 0.032). For secondary exploratory outcomes, significant interactions were observed for trunk extensor endurance and SRS-22 self-image (p < 0.01), with the SCT group showing greater improvement than the CT group specifically at the 6-month follow-up (p < 0.05). In unadjusted exploratory comparisons, trunk flexor endurance was also better in the SCT group at 6 months (p = 0.046). No other significant between-group differences were found. Conclusion Compared with isolated core stabilization training, Schroth 3D scoliosis-specific exercises combined with core training demonstrate superior efficacy in improving early postoperative muscular function, pelvic symmetry, and self-image. Nevertheless, comparable effects were observed between both rehabilitation protocols regarding early postoperative Cobb angles of major and minor curves, convex-concave paraspinal muscle balance restoration, pain alleviation, and psychological status improvement.